Disease In Colonial Assam And Its Effect On Public Health (International Journal of Food and Nutritional Sciences, 2022)
The British had control over the Assam since the treaty of Yandabo which was signed between British government and the Burmese king. Soon after the rule, the britishers faced some diseases which were some known and unknown to them. In the initial days, they didn’t adopt any measures to prevent these diseases. When its started to affecting colonial commercial activities and also heavy losses of lives, colonial government realized to take strict action or policy to prevent from these diseases. Thus they started to implement western medical practices in Assam.